Cleavage of procaryotically expressed human immunodeficiency virus fusion proteins by factor Xa and application in western blot (immunoblot) assays. - Ellinger, S (1989)
The proteins p15 and p24 of the human immunodeficiency virus (HIV) type 1 gag gene were expressed as fusion proteins in Escherichia coli for detecting antibodies against the acquired immunodeficiency virus by Western blot (immunoblot) analysis. These fusion proteins contain amino acids 1 to 375 of the E. coli beta-galactosidase linked to the viral protein(s) by a recognition sequence for the specific protease factor Xa. They are obtained in large amounts in insoluble inclusion bodies. To avoid ambiguous results caused by cross-reaction of sera with bacterial proteins in Western blots, we purified the recombinant fusion proteins and subsequently removed the bacterial part of the fusions by cleavage with factor Xa. The cleavage mixtures were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and blotted onto nitrocellulose membranes. The viral proteins obtained by this method did not contain any bacterial proteins or protein fragments. Thus, false-positive results in HIV Western blot analysis with bacterially expressed HIV proteins can be excluded with these purified recombinant viral antigens.